Clinical characteristics and diagnosis of acute pandysautonomia in childhood - Ding, Chang-hong (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2010)
OBJECTIVE: To summarize the clinical characteristics of acute pandysautonomia in childhood, to gain better understanding of the diagnosis and differential diagnosis